Impact of coronary artery disease in patients undergoing transcatheter aortic valve replacement: Insights from the FRANCE‐2 registry. Issue 12 (16th December 2017) - Puymirat, Etienne; Didier, Romain; Eltchaninoff, Hélène; Lung, Bernard; Collet, Jean‐Philippe; Himbert, Dominique; Durand, Eric; Leguerrier, Alain; Leprince, Pascal; Fajadet, Jean; Teiger, Emmanuel; Chevreul, Karine; et al.
Abstract : Background: Coronary artery disease (CAD) is common in patients undergoing transcatheter aortic valve replacement (TAVR). However, the impact of CAD distribution before TAVR on short‐ and long‐term prognosis remains unclear. Hypothesis: We hypothesized that the long‐term clinical impact differs according to CAD distribution in patients undergoing TAVR using the FRench Aortic National CoreValve and Edwards (FRANCE‐2) registry. Methods: FRANCE‐2 is a national French registry including all consecutive TAVR performed between 2010 and 2012 in 34 centers. Three‐year mortality was assessed in relation to CAD status. CAD was defined as at least 1 coronary stenosis >50%. Results: A total of 4201 patients were enrolled in the registry. For the present analysis, we excluded patients with a history of coronary artery bypass. CAD was reported in 1252 patients (30%). Half of the patients presented with coronary multivessel disease. CAD extent was associated with an increase in cardiovascular risk profile and in logistic EuroSCORE (European System for Cardiac Operative Risk Evaluation) (from 19.3% ± 12.8% to 21.9% ± 13.5%, P < 0.001). Mortality at 30 days and 3 years was 9% and 44%, respectively, in the overall population. In multivariate analyses, neither the presence nor the extent of CAD was associated with mortality at 3 years (presence of CAD, hazard ratio [HR]: 0.90; 95% confidence interval [CI]: 0.78‐1.07). A significant lesion of the left anterior descending (LAD) was associated with higher 3‐year mortality (HR: 1.42; 95% CI: 1.10‐1.87). Conclusions: CAD is not associated with decreased short‐ and long‐term survival in patients undergoing TAVR. The potential deleterious effect of LAD disease on long‐term survival and the need for revascularization before or at the time of TAVR should be validated in a randomized control trial.